Empirical Estimation of Fiscal Multipliers in MENA Oil-Exporting Countries with an Application to Algeria - Elkhdari, Maria (IMF Working Papers; Working Paper ;, 2018)
At a time when Algeria must undertake considerable fiscal consolidation to restore sustainability, the issue of fiscal multipliers has come to the fore. This paper estimates short-term and long-term fiscal multipliers for Algeria applying several econometric methodologies, including Local Projection Methodology and Vector Autoregressive Models, and using both Algeria-specific and panel data. The paper also explores asymmetries related to the sign of the output gap as well as the direction of spending. The results suggest that (i) average fiscal multipliers for Algeria are generally moderate and below unity; (ii) the impact of public spending shocks is more important when the output gap is negative; (iii) fiscal spending multipliers are significantly larger during spending contraction than expansion; (iv) procyclicality in public spending does not appear to affect output, except for capital spending cuts when the output gap is negative; and (v) while multipliers associated with countercyclical public spending can be sizeable, a contraction in current spending does not materially affect non-oil GDP.